Timing of excision after a non-severe burn has a significant impact on the subsequent immune response in a murine model. Issue 4 (June 2016) - Fear, Vanessa S.; Poh, Wee-Peng; Valvis, Samantha; Waithman, Jason C.; Foley, Bree; Wood, Fiona M.; Fear, Mark W.
Highlights: Timing of excision impacts on the immune response after burn. Late excision (day 8 in model) exacerbates inflammatory response to burn. Late excision reduces later cellular responses. Early excision maintains innate and adaptive response to the injury. Abstract: Background: Burn excision has emerged as the dominant clinical paradigm in treatment of deep burns. Surgical intervention is common but the timing of wound excision is a balance between wound depth assessment, avoidance of infection and unnecessary intervention. However the physiological impact of timing of excision and consequences for the immune response are not well understood. Methods: Mice were subject to full-thickness burn (<8% TBSA) followed by early (day 1) or late (day 8) surgical excision. Draining lymph nodes, wound tissue and sera were collected longitudinally at day 2 and day 6 after excision and analyzed for cytokine, dendritic cell and T cell profiles using FACS and multiplex ELISA assays. Results: Delayed excision after injury initiated acute and severe inflammatory responses, with high levels of inflammatory cytokines, increased chemokine responses, and elevated Th2 promoting cytokines compared to early excision. Cellular inflammation in the wound was exacerbated with elevated neutrophils, eosinophil and monocytes. Wound cellular innate immune response decreased after late excision with a loss of inflammatory dendritic cells (DC), decreased NKT cells, and inhibition of NK cell activation. Systemically late excision increased trafficking conventional CD8α − DC to the lymph node, but there was no apparent DC activation. This was reflected in the induction of CD4T regulatory (Treg) cells and suppression of CD8T cell proliferation after late excision. No suppression was observed with early excision. Conclusion: This data suggests early excision of the wound, during the phase of immune down-regulation initiated by the burn, maintains an innate and adaptive immune cell response. In contrast, late wound excision induced a severe inflammatory response, with subsequent down-regulation of innate and adaptive immune cell responses. Therefore timing of excision is critical in affecting the immune response to burn.